1996
DOI: 10.1084/jem.183.4.1367
|View full text |Cite
|
Sign up to set email alerts
|

Visualization, characterization, and turnover of CD8+ memory T cells in virus-infected hosts.

Abstract: SummaryThe cellular basis of T cell memory is a controversial issue and progress has been hampered by the inability to induce and to trace long-term memory T cells specific for a defined antigen in vivo. By using the murine model of lymphocytic choriomeningitis virus (LCMV) infection and an adoptive transfer system with CD8 § T cells from transgenic mice expressing an LCMV-specific T cell receptor, a population of authentic memory T cells specific for LCMV was generated and analyzed in vivo. The transferred tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
193
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(211 citation statements)
references
References 49 publications
17
193
0
Order By: Relevance
“…The Ag-primed CD8 ϩ T cells use specific T cell receptors to lyse infected cells presenting virus-derived peptides bound to MHC-class I molecules. Following the effector phase, T cell numbers contract and Ͼ90% of the total population is eliminated (1,2). The reduction in cell counts results from the withdrawal of survival factors, (3) and from increased levels of apoptotic signals that trigger activationinduced cell death (AICD).…”
Section: Irus Infections Induce the Expansion And Differentiationmentioning
confidence: 99%
“…The Ag-primed CD8 ϩ T cells use specific T cell receptors to lyse infected cells presenting virus-derived peptides bound to MHC-class I molecules. Following the effector phase, T cell numbers contract and Ͼ90% of the total population is eliminated (1,2). The reduction in cell counts results from the withdrawal of survival factors, (3) and from increased levels of apoptotic signals that trigger activationinduced cell death (AICD).…”
Section: Irus Infections Induce the Expansion And Differentiationmentioning
confidence: 99%
“…The CD62L + CD44 low/+ phenotype is thought to represent the naive T cell population whereas CD62L dull CD44 bright and CD62L -CD44 bright phenotypes typify primed T cells [34]. In every compartment CD8 + CD27 -cells were completely excluded from the CD62L + CD44 low/+ (unprimed) T cell population.…”
Section: Days)mentioning
confidence: 99%
“…Peripheral blood was collected from euthanized mice via cardiac puncture and treated with 0.5 mM EDTA and stained with the appropriate mAb. Erythrocytes were lysed in 0.84% NH 4 Cl and washed twice with Iscove's modified Dulbecco's medium (BioWhittaker, Walkersville, MD) containing 10% FBS, 2 mM Lglutamine and antibiotics (complete medium). Aliquots were used for FACS analysis.…”
Section: Organ Isolationmentioning
confidence: 99%
“…Subsequently, CD11b was demonstrated as an activation marker for CD8 + CTL during a virus infection [1]. Some reports have shown that CD11b expression becomes down-regulated when CD8 + T cells enter the memory phase, which could be used to phenotypically distinguish recently activated effectors cells from memory cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%